Interaction between 24 h Urinary Free Cortisol and Obesity in Hypertension-Mediated Organ Damage in Patients with Untreated Hypertension - Gao-Zhen Cao; Jia-Yi Huang; Qing-Shan Lin; Cong Chen; Min Wu; Run Wang; Ming-Yen Ng; Kai-Hang Yiu; Jian-Cheng Xiu (Reviews in Cardiovascular Medicine)
Background: Given the close relationship between excessive cortisol secretion and obesity, as well as their intimate associations with cardiometabolic sequelae, this study aimed to evaluate whether elevated cortisol levels and obesity are independently and potentially interactively related to hypertension-mediated organ damage (HMOD) in patients with untreated hypertension. Methods: A total of 936 untreated hypertensive patients were recruited. Body mass index (BMI), 24-hour urinary free cortisol (24 h UFC), and HMOD indicators, including left ventricular hypertrophy (LVH), carotid intima-media thickness (CIMT), and albuminuria, were assessed. Multivariate logistic regression was conducted to evaluate the associations of HMOD indicators with 24 h UFC and obesity. Generalized linear models were used to test for the interaction effects of obesity in the associations between log 24 h UFC levels and HMOD indicators. Results: Compared to non-obese patients, those who were obese had a greater left ventricular mass index (LVMI), greater CIMT, a higher level of 24-hour urinary albumin (24 h UALB) and more frequent albuminuria (all p < 0.05). In the obese group, elevated 24 h UFC was significantly associated with LVH (odds ratio (OR) = 2.53; 95% CI: 1.02–6.31, p = 0.044) and albuminuria (OR = 3.13; 95% CI: 1.31–7.43, p = 0.01), after multivariate adjusting. There was a significant interactive effect of obesity on the association between 24 h UFC and LVH and albuminuria (all p for interaction <0.05). A significant correlation was observed between 24 h UFC and LVMI in obese and non-obese patients. Conversely, the correlations of 24 h UFC and log 24 h UALB were found only in obese patients but not in non-obese patients. Conclusions: Elevated 24 h UFC levels were associated with higher severity of HMOD, including more frequent LVH, albuminuria, and greater CIMT. Additionally, obesity modified the effects of 24 h UFC on both LVH and albuminuria.